Clostridium difficile recurrent infection: possible implication of TA systems. (October 2015) - Gil, Fernando; Pizarro-Guajardo, Marjorie; Álvarez, Ricardo; Garavaglia, Marco; Paredes-Sabja, Daniel
Clostridium difficile is an important nosocomial pathogen associated with antibiotic treatments. C . difficile 's ability to survive antimicrobial therapy and transition from inert colonization to active infection is one of the most perplexing aspects of C. difficile infections and suggests that additional mechanisms are involved in persistence. In this regard, novel mechanisms linked with pathogenesis and persistence of C . difficile such as toxin–antitoxin systems might significantly contribute to biofilm formation and persistent infection. This review will focus on advances of toxin–antitoxin systems in C. difficile and their putative roles will be discussed.